Cardiac arrest and pregnancy - Campbell Tabitha (Journal of Emergencies, Trauma and Shock, 2009)
Cardiopulmonary arrest in pregnancy is rare occurring in 1 in 30,000 pregnancies. When it does occur, it is important for a clinician to be familiar with the features peculiar to the pregnant state. Knowledge of the anatomic and physiologic changes of pregnancy is helpful in the treatment and diagnosis. Although the main focus should be on the mother, it should not be forgotten that there is another potential life at stake. Resuscitation of the mother is performed in the same manner as in any other patient, except for a few minor adjustments because of the changes of pregnancy. The specialties of obstetrics and neonatology should be involved early in the process to ensure appropriate treatment of both mother and the newborn. This article will explore the changes that occur in pregnancy and their impact on treatment. The common causes of maternal cardiac arrest will be discussed briefly.